A Monte Carlo study of leading order scaling corrections of φ4 theory on a three-dimensional lattice - Hasenbusch, Martin (Journal of physics. A, Mathematical and general, 1999)
We present a Monte Carlo study of the one-component 4 model on a cubic lattice in three dimensions. Leading order scaling corrections are studied using the finite size scaling method. We compute the corrections to scaling exponent with high precision. We determine the value of the coupling at which leading order corrections to scaling vanish. Using this result we obtain estimates for critical exponents that are more precise than those obtained with field-theoretic methods.
Gesehen am 28.09.2022
Im Titel ist die Zahl 4 hochgestellt